Prevalence of anxiety disorders and its associated factors among adolescents in Arpookara Panchayat - S., Rani Suhra; A., Sobha; M., Geethadevi; B., Prithiba; Philip, Sairu (International Journal Of Community Medicine And Public Health, 2023)
Background: Adolescents (10 -19 years) constitute 1.3 billion in the world today. According to WHO mental health issues constitute 13% of the global burden of disease in adolescents of which anxiety disorders are the most common. Objective was to estimate the prevalence of anxiety disorders among adolescents using SCARED tool, to find the association of selected factors with anxiety disorders. Methods: A cross sectional study was conducted among 590 adolescents in Arpookara Panchayat. A semi-structured pretested questionnaire was used for collecting sociodemographic details. Anxiety disorder was assessed using Screen for Child Anxiety Related Emotional Disorder (SCARED) tool. Data was coded and entered in Microsoft excel and analysed using IBM SPSS software version 20 Results: The mean age of the study participants was 15.04 with SD ±3.013. Prevalence of anxiety disorders using SCARED tool was found to be 21.4%. Factors found to have statistically significant association with anxiety on univariate analysis were female gender (p=0.001), mother’s education more than high school level (p=0.036), time spent with father (p=0.001), time spent with mother(p=0.001), inadequate sleep (p=0.001) and family history of mental illness(p=0.043). On binary logistic regression following factors with p<0.05 were found to be independent predictors of anxiety-female gender (OR=2.037), mother’s education more than high school level (OR=1.469) adequate time spent with father (OR=0.713), inadequate sleep (OR=14.726), family history of mental illness (OR=3.521) Conclusions: More than one fifth of adolescents are having anxiety disorders. There should be efforts for early diagnosis and prompt treatment of anxiety disorders among adolescents.